Treatment-related Cardiovascular Toxicity in Long-term Survivors of Testicular Cancer - Gugic, Jasenka (Radiol Oncol, 2016)
BACKGROUNDS: Testicular cancer is the most common malignancy in young men. Considering increasing incidence, exceptionally high cure rate, as well as long life expectancy, assessment of long term toxicity in testicular cancer survivors is of great importance. In the last decades a major effort has been made in order to reduce toxicity of treatment, while maintaining its high effectiveness. CONCLUSIONS: Actual knowledge on treatment toxicity is based on outdated treatment modalities. Hopefully, modern treatment modalities could reduce toxicity, but, there is no firm confirmation for that at the moment, as data dealing with late sequelae of modern treatment of testicular cancer are not available yet due to the short period of observation. The life-threatening cardiovascular toxicity in testicular cancer survivors is major complication of platinum-based chemotherapy, mediastinal radiotherapy and even subdiaphragmatic radiotherapy.